Recent Books on Business Cycles - Hardy, Charles O.; Jordan, David F; Lavington, F.; Pell, Charles Edward (Quarterly Journal of Economics, 1923)
Recent Books on Business Cycles F. Ernest Richter F. Ernest Richter New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 1, November 1923, Pages 153–168, https://doi.org/10.2307/1885774 Published: 01 November 1923